If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(t + 5) = -36 Reorder the terms: -3(5 + t) = -36 (5 * -3 + t * -3) = -36 (-15 + -3t) = -36 Solving -15 + -3t = -36 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -3t = -36 + 15 Combine like terms: -15 + 15 = 0 0 + -3t = -36 + 15 -3t = -36 + 15 Combine like terms: -36 + 15 = -21 -3t = -21 Divide each side by '-3'. t = 7 Simplifying t = 7
| 12(23x+46y)+23=762 | | 5t^2-13t-2=0 | | 20x/24 | | x^3+25x-3=0 | | -x-29=4x+11 | | 17t-3t+8t+17t=-11 | | 36+x=4(6+x) | | 1a+2b+3c=4d | | 4a+6=2a-10 | | 3(2+5)=15 | | 1x+2y=3x | | -1=3r+22 | | 115x+935x=1 | | 16p-15p+3p-3p=15 | | -10(s+4)=-73 | | 115x+935x=9000 | | 2w+5-4w=7-4w | | 10=7+5t | | 1x+2+3+4+5+6+7+8+9=9001 | | 4tanx=3+tanx | | Y-4=-1(x-(-3)) | | 2w+6-2(-9w-4)=4(w-1) | | 7/4=x/100 | | 9k-k-k-6k+k=14 | | 48-2n=16 | | 10r-4r=12 | | 42-2n=16 | | -5n+(6+6n)=3(3n+2) | | 3c-1.6+2.5c=.5+2c-9.1 | | 2x+3y=69 | | (78*.4)+(44*.4)+(x*.2)=61 | | (82*.4)+(65*.4)+(x*.2)=61 |